Disharmoni Negara dan Pasar Dalam Rezim Neoliberal - Ade Marup Wirasenjaya (Jurnal Hubungan Internasional, 2013)
This article tries to explain that the neoliberal regime has created an unequal relationship between state and market, especially in developing countries. The relationship between state and markets in developed countries have a different mode than similar relationship in developing countries. In developed countries, the mode of the state and market relations is “state make market”. By contrast, in developing countries, the mode is “market make-state” relation. As a result of two different modes that is, neo-liberalism gave birth to the patterns of disharmony in developing countries. It brings disharmony due to domestic political life and in the context of struggle of the state in international politicaleconomy.